PERILAKU KADER DALAM PEMANTAUAN PERTUMBUHAN BALITA DI PUSKESMAS MANDALA KECAMATAN MEDAN TEMBUNG - Hastaty HS; Zulhaida Lubis; Jumirah . (Lingkungan dan Kesehatan Kerja, 2015)
The cadres failure in the implementation of health center activities to monitor the growth of children under five will result in the wrong conclusion which will give incorrect information and precaution. Therefore, an analyze is required to determine the behavior of cadres in monitoring the growth of children under five in Mandala health center in sub district Medan Tembung. This research is a descriptive cross sectional design research carried out in September 2013 to December 2014. The population in this study were all cadres in 39 integreted health posts in working area of public health center Mandala district of Medan Tembung that is 159 people. The sample in this study were 100 people who is obtained using cluster sampling. Existing data will be analyzed descriptively and presented in form of a frequency distribution table. The result of this research showed that 51,0% cadres aged < 37 years old; 61,0% of cadres education is primary education (Primary Junior High School); 90,0% has becomed cadres for > 2 years; unemployed caders is 83,0%; and the most frequent task is the registration (41,0%). Cadre behaviour in implementation of children under five year growth monitoring, 49,0% of cadre has good knowledge, but only 14,0% cadre has good manner and only 3,0% cadre with good action. It is suggested for the clinic to give education to the cadres in growth monitoring of children under five and to provide training such as plotting training, weighting children under five and calculating ages periodacally to the cadres. Keywords: Growth Monitoring of Children Under Five, Behaviour, Cadres